ANALISIS KUALITAS PELAYANAN AKTA KELAHIRAN GRATIS (BEBAS BEA) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KLATEN - Dina Aprita Sari; Nina Widowati; Aloysius Rengga (Journal of Public Policy and Management Review, 2014)
In deal with a public demand of an excellent public service, it becomes a challenge for the Department of Population and Civil Registry of District Klaten in order to create a service quality in accordance with public expectations. Through this study, the researcher wanted to analyze the quality of free birth certificate services that available in Department of Population and Civil Registry of District Klaten. The dimensions of service quality that will be investigated are tangible dimension, reliability dimension, responsiveness dimension, assurance dimension, and empathy dimension. Based on the research that has been done, it can be seen that the service quality of free birth certificate in the Department of Population and Civil Registry of District Klaten is not optimal or unsatisfactory. The problems are found in the dimensions of reliability, responsiveness, and assurance. In connection with the service quality that has not been optimal, it is necessary to do improvement to the problems that found in every dimension.